2008
DOI: 10.1017/s1049023x00064943
|View full text |Cite
|
Sign up to set email alerts
|

Trial of a Survey Instrument to Establish the Hurricane Preparedness of and Medical Impact on a Vulnerable, Older Population

Abstract: Introduction: Millions of vulnerable, elderly individuals live in coastal areas susceptible to hurricanes and are at risk for adverse health outcomes. The purpose of this study was to determine the status of preparedness for and possible health consequences of a hurricane on a vulnerable, but experienced, elderly population.Problem: Preparedness guidelines have been published, but it is unclear how well-prepared elderly individuals are for hurricanes, and what impact hurricanes may have on their health.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…In our study, most residents identified television as the main ways to get information before typhoon (83.5%), the result was similar with previous studies in China [14,28], Florida [26], and New Jersey [34]. TV is a major and convenient source of information among rural residents.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In our study, most residents identified television as the main ways to get information before typhoon (83.5%), the result was similar with previous studies in China [14,28], Florida [26], and New Jersey [34]. TV is a major and convenient source of information among rural residents.…”
Section: Discussionsupporting
confidence: 89%
“…In some cases, while residents generally felt prepared for a typhoon disaster, it has been found that there was in fact still insufficient preparation [25]. Even people who had experienced typhoon many times might not take adequate typhoon preparation actions, which increased population vulnerability [26]. A study in Iran showed that the knowledge of people regarding disaster preparedness was encouraging, but the translation of knowledge into effective attitudes and appropriate practices was weak [27].…”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30]53 Previous research focusing on individual preparedness, response to disasters, and expectations of future disasters have revealed disparities in race=ethnicity, social class, gender, and age. 12,15,[54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69] Given the differential experiences during disasters based on group membership, it is not surprising that a lack of trust in public authorities exists among some subgroups. [70][71][72] Because of this mistrust, culturally appropriate preparedness information is a critical component of preparedness efforts for all individuals.…”
mentioning
confidence: 99%
“…A fair question to ask would be-just how disaster prepared are the elderly in general? A study carried out by Cherniack and coworkers sought to answer this important question (Cherniack et al 2008). The authors surveyed 547 ambulatory elderly patients attending a Florida urban teaching hospital's geriatric clinic in the wake of the 2005 Hurricane Wilma.…”
Section: How Disaster Prepared Are the Elderly?mentioning
confidence: 99%